Factors affecting social learning in nearby pockets on tropical campus grounds: towards a sustainable campus - Alzamil, Waleed; Abdulkareem Salih, Sarah; Ismail, Sumarni; Ajlan, Ali; Azmi, Athira (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Nearby natural environments on campus grounds have become imperative in enhancing sustainable academic experiences by facilitating sustainable social learning. However, tropical region campuses prioritise traditional education while neglecting sustainable social learning. Therefore, the purpose of this study was to facilitate the use of nearby sustainable pocket settings on campus grounds to enhance social learning experiences. The present study aimed to identify factors affecting social learning experiences in nearby (sustainable) pocket spaces on tropical campuses. It utilised a verbal questionnaire survey conducted in three research universities in Malaysia to investigate the factors affecting 408 respondents in nearby (sustainable) pockets. The respondents were selected using stratified judgemental sampling. This study’s findings revealed that many influencing factors predicted the social learning experience in tropical universities’ nearby pockets, which were arranged into four domain factors: elements and activities, natural environment factors, perceived environment factors, and social factors. This provided a proven correlation between the lack of social learning in nearby pockets and the factors of these sustainable settings. The findings also showed that students’ demographic factors, including education status and university affiliation, influenced their social learning experience. The present study significantly linked education to sustainability by integrating social learning into nearby sustainable pocket settings.